Associations of Chronotype and Sleep With Cardiovascular Diseases and Type 2 Diabetes. (2013) - Merikanto, Ilona; Lahti, Tuuli; Puolijoki, Hannu; Vanhala, Mauno; Peltonen, Markku; Laatikainen, Tiina; Vartiainen, Erkki; Salomaa, Veikko; Kronholm, Erkki; Partonen, Timo
Abstract : In this study, the authors analyzed whether chronotypes, sleep duration, and sleep sufficiency are associated with cardiovascular diseases and type 2 diabetes by using the National FINRISK Study 2007 data (N = 6258), being a representative sample of the population aged 25 to 74 living in five areas of Finland. Health status assessments and laboratory measurements from the participants (N = 4589) of the DILGOM substudy were used for the detailed analysis of chronotype. Evening types had a 2.5-fold odds ratio for type 2 diabetes ( p < .01) as compared with morning types, the association being independent of sleep duration and sleep sufficiency. Evening types had a 1.3-fold odds ratio for arterial hypertension ( p < .05 after controlling for sleep duration or sleep sufficiency), a faster resting heart rate and a lower systolic blood pressure (both p < .01), and lower levels of serum total cholesterol and low-density lipoprotein cholesterol (both p < .0001) than morning types. There were significant 1.2- to 1.4-fold odds ratios for arterial hypertension among those with long or short sleep durations or reduced sleep sufficiency. To conclude, the behavioral trait towards eveningness is suggested to predispose individuals to type 2 diabetes in particular, whereas compromised sleep is robustly associated with arterial hypertension. (Author correspondence:ilona.merikanto@helsinki.fi )